(untitled) (Raparin Journal of Humanities (RJH), 2025)
This paper explores the psychological dimensions of aggression, irritability, and sadism as portrayed in Dean Koontz’s novel Intensity, focusing on the character of Edgler Vess. The analysis applies psychological theories, particularly those of Erich Fromm and Alfred Adler, to reveal the underlying psychological mechanisms that drive Vess’s antisocial behavior. Through the application of Fromm’s concepts of malignant aggression, sadism, and necrophilia alongside Adler’s theory of overcompensation, the paper examines how Vess’s sadistic tendencies, violent actions, and obsession with death reflect broader human capacities for destruction and domination. By analyzing key scenes in the novel, the study illustrates how Vess’s violent actions are not just expressions of random aggression but are driven by deep psychological needs for control, power, and existential fulfillment. The significance of the study lies in its ability to bridge literary analysis with psychological theory, offering new insights into the representation of pathological aggression in literature. The study concludes that Vess embodies the extreme end of human destructiveness, highlighting how unresolved psychological conflicts can manifest into pathological behavior. This analysis positions Intensity not just as a thriller, but as a profound commentary on the extremes of human nature and the terrifying capacity for cruelty when violence becomes a means of existential self-assertion.